Marginalised young people's healthcare journeys: Professionals' perspectives. (October 2018) - Robards, Fiona; Kang, Melissa; Tolley, Kate; Hawke, Catherine; Sanci, Lena; Usherwood, Tim
Introduction: The pursuit of social justice includes a commitment to health equity for marginalised young people. Health professionals are central to marginalised young people's engagement and access to health care and their navigation of health systems. They are also uniquely positioned to shed insight into structures and inefficiencies within the health system, including the role of technology, and to advocate for system change. Methods: This qualitative cross-sectional study employed in-depth semi-structured interviews with 22 health service managers and experienced clinicians to better understand service providers' perspectives. The sampling frame comprised professionals from different sectors and levels of the health system. Analysis used Grounded Theory methods. Results: Three major themes were identified in the data: (1) intersectionalities – understanding the complexity of multiple disadvantage; (2) health system fragmentation – leading to inefficiencies, inertia and advocacy; and (3) services needing to be 'turned on their head' – rethinking service delivery and models of care. Conclusion: A better understanding of marginalised young people's healthcare experiences, including the complexities of multiple disadvantage, and how this contributes to health inequalities could lead to more welcoming and respectful services. Services can reconceptualise their roles by reaching out to young people, both physically and online, to make the navigation of the health system easier. Marginalised young people's healthcare journeys can be supported by advocates that help them navigate the health system.